Influence of genetics on fertility traits in Angus bulls - Stock, Danielle Marie (My University, 2024)
Whether a bull is used for natural mating or artificial insemination (AI), a single bull with suboptimal fertility can have a greater impact on herd productivity compared to a single female with reduced fertility. Despite this, extensive research on advanced reproductive technologies and genetic evaluations has focused primarily on female fertility, leaving a gap in the understanding of factors influencing male fertility. Therefore, the objectives of this study were to estimate the genetic parameters for scrotal circumference, sperm motility, and sperm morphology traits, evaluate the utility of combining breeding soundness examination (BSE) and AI bull stud collection data, and perform a genome-wide association study. Breeding soundness examination data were obtained from 4,996 Angus bulls, and stud collection data were obtained from 1,862 Angus stud bulls. The data were analyzed as a BSE dataset, a stud dataset, and a combined dataset with both BSE and stud records. Each of the three datasets were evaluated individually for genetic parameters. A single-step genomic best linear unbiased prediction (ssGBLUP) was used to estimate variance components and heritabilities of bull reproductive traits with the BLUPF90+ suite of programs (Misztal et al., 2014). The heritabilities estimated for scrotal circumference ranged from 0.36 to 0.55, while semen motility and morphology traits had lower heritability estimates of 0.04 to 0.12. Phenotypic and genetic correlations across traits in a single dataset ranged from low to high. Additionally, genetic correlations were estimated within traits to assess the relationship between a measurement taken during a BSE and at a bull stud, which resulted in low to moderate correlations. The significant quantitative trait loci (QTL) regions in the genome were identified at a significance threshold of -log10 P-value greater than 4.0 for scrotal circumference (SC), percentage of progressive motility (%MOT), motility score (MOTSC), percentage of secondary abnormalities (%SEC), and percentage of normal spermatozoa (%NORM). Previously reported QTL and candidate genes associated with fertility traits were identified. Results indicate that bull fertility is influenced by genetics, and selecting bulls with enhanced fertility could improve reproductive efficiency and herd productivity.
Keywords: Beef bull; Reproduction; Heritability; Correlation; Genome-wide association study